The Effect of Fermentation Time on Product Quality of Starfruit Juice Probiotic Drinks with Starter Culture L. plantarum B1765 - Islahah, Nur; Wikandari, Prima R (Universitas Pattimura, 2022)
This study aims to determine the effect of fermentation time on microbiological (total lactic acid bacteria), chemistry (pH, total titrated acid) and organoleptic (color, aroma, and flavor) qualities of the product of the starfruit (Averrhoa carambola L.) probiotic juice drink cultured by L. plantarum B1765. L. plantarum B1765 had been studied has potency as probiotics candidate. The fermentation time used is 0, 6, 18, and 24 hours. Total lactic acid bacteria (LAB) are tested by the total plate count (TPC) method, pH tested with a pH meter, total titrable acidity (TTA) tested with acid-base titration, and organoleptic tested by the hedonic scale method. The length time of fermentation affects the total lactic acid bacteria (LAB), pH, and TTA and shows a significant difference up to 18 hours of fermentation. Total BAL increased from 1.08 × 108 to 4.20 × 108 CFU/ml. pH dropped from 3.80 to 3.18. TTA increased from 0.44% to 0.81%. The organoleptic test shows the level of preference for the color, aroma, and flavor at the best fermentation time for 18 hours with a successive value of 3.20; 3.20; and 3.30 with the like category. The starfruit juice fermented by L. plantarum B1765 is potencial as a probiotic agent drink.